Sustainable Living with Environmental Risks - Kaneko, Nobuhiro; Yoshiura, Shinji; Kobayashi, Masanori; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2014)
We are not free from environmental risks that accompany the development of human societies. Modern economic development has accelerated environmental pollution, caused loss of natural habitats, and modified landscapes. These environmental changes have impacted natural systems: water and heat circulation, nutrient cycling, and biodiversity. These changes in natural systems degrade ecosystem services and subsequently increase environmental risks for humans. Environmental risks, therefore, are not only human health risks by pollution, climatic anomalies, and natural disasters, but also degradation of ecosystem services on which most people are relying for their lives. We cannot entirely eliminate the risks, because it is not possible to attain zero impact on the environment, but we need to find a mechanism that minimizes environmental risks for human sustainably. This is the idea of the interdisciplinary framework of (3z(Benvironmental risk management(3y (Btheory, which advocates harmony betweeneconomic development and environmental conservation. Based on this theory, the Sustainable Living with Environmental Risk (SLER) programme, adopted by the Japanese Ministry of Education (MEXT) as one of its strategic programmes, has been training graduate students at the Yokohama National University, Japan, from 2009 to 2013 to become future environmental leaders who will take the initiative in reducing the level of environmental risks and in protecting natural resources in the developing nations of Asia and Africa. This book provides students and teachers of this new academic field with a comprehensive coverage of case studies of environmental risks and their practical management technologies not only in Japan but also in developing nations in Asia and Africa.s
Managing Environmental Risks and Promoting Sustainability: Science Advancement and Leadership Development -- Biodiversity Agriculture Supports Human Populations -- Conservation and Sustainable Management of Soil Biodiversity for Agricultural Productivity -- Conservation Tillage Assessment For Mitigating Greenhouse Gas Emission In Rainfed Agro-Ecosystem -- Improving Biodiversity in Rice Paddy Fields to Promote Land Sustainability -- Agroforestry Models for Promoting Effective Risk Management and Building Sustainable Communities -- Managing Environmental Risks and Promoting Sustainability: Conservation of Forest Resources in Madagascar -- Community-Based Mangrove Forest Management in Thailand: Key Lesson Learned for Environmental Risk Management -- Necessity of Adaptive Risk Management for Fisheries and Wildlife -- Valuation of Non-Marketed Agricultural Ecosystem Services and Food Security in Southeast Asia -- Emerging Socio-Economic and Environmental Issues Affecting Food Security: A Case Study of Silang-Santa Rosa Subwatershed -- Strengthening the Capacity of Flood-Affected Rural Communities in Padang Terap, State of Kedah, Malaysia -- Mitigating Coastal Erosion in Fort Dauphin, Madagascar -- Risk Management of Chemical Pollution: Principles from the Japanese Experience -- Research on the Sod Between Chlorophyll-a and Organic Matter BOD, COD, Phosphorus and Total Nitrogen in Stagnant Lake Basins -- Managing Construction Development Risks to the Environment -- Ecosystem Restoration Using the Near-Natural Method in Shanghai -- Sustainable Management of Urban Green Environments: Challenges and Opportunities -- Environment and Social Capacity Assessment for Sustainability Promotion and Risk Management -- Rural Landscape Conservation in Japan: Lessons from the Satoyama Conservation Program in Kanagawa Prefecture -- Enhancing Students$1 (BEcological Thinking to Improve Understanding of Environmental Risk -- Interactive Multimedia Education System (IMES) as a International Education Platform.s
Keywords: Physical geography; Environmental management; Sustainability; Earth System Sciences; Environmental Management; Sustainability